A Detailed Analysis of a Resonant Gate Driver for PWM Applications - Dürbaum, Thomas; et al. (18th Annual Applied Power Electronics Conference, APEC 2003, 2003)
Gate drivers generate significant losses, especially at high frequencies. While conventional solutions dissipate all the energy, resonant gate drivers partly recover it. A resonant gate driver is studied in detail with the emphasis on PWM operation. Compared to other resonant drivers, the investigated driver combines simplicity, fast switching and loss reduction. Advantages and limits are discussed using a mathematical model and a prototype.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.lselek.adetai
Keywords: Power Loss Reduction; PWM Control; Resonant Gate Drivers